Spatial and temporal variability of dissolved methane concentrations and diffusive emissions in the Three Gorges Reservoir. (1st December 2021) - Liu, Jia; Xiao, Shangbin; Wang, Chenghao; Yang, Zhengjian; Liu, Defu; Guo, Xiaojuan; Liu, Liu; Lorke, Andreas
Highlights: We conducted high-resolution dissolved CH4 measurements in the Three Gorges Reservoir. Strong spatial and temporal variability of dissolved CH4 concentrations was observed. The upstream sections had higher dissolved CH4 concentrations and diffusive fluxes. Dissolved CH4 was characterized by sewage discharge, water depth, and electrical conductivity. We evaluated the minimum sampling effort for high-accuracy concentration measurements. Abstract: Methane (CH4 ) emissions from freshwater aquatic systems such as rivers and reservoirs are an important component of the global methane budget. However, the estimation can be largely affected by the spatial and temporal resolutions of measurements. Especially, the lack of high-resolution studies in the Three Gorges Reservoir (TGR), one of the largest reservoirs in the world, has led to a longstanding debate on its CH4 emissions. In this study, the spatial distribution and seasonal variations of dissolved CH4 concentrations were measured using a fast-response automated gas equilibrator in the TGR. We observed large spatiotemporal variations of dissolved CH4 (mean ± SD: 0.26 ± 0.19 μM in summer and 0.24 ± 0.17 μM in winter). Higher concentrations with stronger variations were found in the upstream than in the section close to the Three Gorges Dam. The dissolved CH4 concentration in the TGR was mainly influenced by sewage discharge, sedimentation, topographical conditions, tributaries, and spatial and seasonal variations in hydrodynamics. Regression analyses suggest that the concentration can be characterized by sewage discharge, water depth, and electrical conductivity to a certain extent. Mean diffusive CH4 fluxes from the TGR in summer and winter were 16.2 mg m − 2 d − 1 and 3.1 mg m − 2 d − 1, respectively. Downsampling simulations show that scaling dissolved CH4 in the TGR from one site likely involves large errors, and at least ∼38 sites and ∼52–58 sites are needed to achieve an accurate estimate in summer and winter, respectively. Due to the large spatial and temporal heterogeneity, high-resolution measurements are key to improving the reliability of CH4 estimates and assessing the contribution of the TGR to regional and global CH4 budgets. Graphical abstract: Image, graphical abstract